Cartilage mechanical tests: Evolution of current standards for cartilage repair and tissue engineering. A literature review. (August 2019) - Marchiori, Gregorio; Berni, Matteo; Boi, Marco; Filardo, Giuseppe
Abstract: Background: Repair procedures and tissue engineering are solutions available in the clinical practice for the treatment of damaged articular cartilage. Regulatory bodies defined the requirements that any products, intended to regenerate cartilage, should have to be applied. In order to verify these requirements, the Food and Drug Administration (FDA, USA) and the International Standard Organization (ISO) indicated some Standard tests, which allow evaluating, in a reproducible way, the performances of scaffolds/treatments for cartilage tissue regeneration. Methods: A review of the literature about cartilage mechanical characterization found 394 studies, from 1970 to date. They were classified by material (simulated/animal/human cartilage) and method (theoretical/applied; static/dynamic; standard/non-standard study), and analyzed by nation and year of publication. Findings: While Standard methods for cartilage mechanical characterization still refer to studies developed in the eighties, expertise and interest on cartilage mechanics research are evolving continuously and internationally, with studies both in vitro – on human and animal tissues – and in silico, dealing with tissue function and modelling, using static and dynamic loading conditions. Interpretation: there is a consensus on the importance of mechanical characterization that should be considered to evaluate cartilage treatments. Still, relative Standards need to be updated to describe advanced constructs and procedures for cartilage regeneration in a more exhaustive way. The use of the more complex, fibre-reinforced biphasic model, instead of the standard simple biphasic model, to describe cartilage response to loading, and the standardisation of dynamic tests can represent a first step in this direction. Highlights: A review of research studies on cartilage mechanics was conducted. Research studies are evolving cartilage mechanical models and characterizations. Mechanical tests are fundamental for developing products to regenerate cartilage. Mechanical standards on regenerated cartilage need to be updated. Improved standards should describe cartilage by a fibre-reinforced biphasic model.